2020
DOI: 10.1111/jog.14213
|View full text |Cite
|
Sign up to set email alerts
|

Huge broad ligament leiomyoma with cystic degeneration: A diagnostic and surgical challenge

Abstract: Broad ligament is the common extrauterine site for fibroid. We present a case of huge broad ligament fibroid with cystic degeneration. Patient presented with abdominal swelling and mild pain abdomen. On abdominal examination, a large tense cystic mass of 34 weeks gravid uterus size arising from pelvis was noted. Cervix was pulled up and all fornices were full with mass on pelvic examination. Ultrasound suggested adnexal mass as ovaries were not seen. Contrast-enhanced computed tomography abdomen too reported a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Leiomyomas are the most common benign tumors of the female genital tract 1 . They arise most often from the uterus, but can also grow on other extrauterine sites, from which the broad ligament is the commonest 3 . Kelly and Cullen were the first to describe parasitic fibroids in 1909 4…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Leiomyomas are the most common benign tumors of the female genital tract 1 . They arise most often from the uterus, but can also grow on other extrauterine sites, from which the broad ligament is the commonest 3 . Kelly and Cullen were the first to describe parasitic fibroids in 1909 4…”
Section: Discussionmentioning
confidence: 99%
“…As doing so, the attachment to the uterus is lost 4 . Additionally, it has been suggested that leiomyomas adherent to the broad ligament originate directly from hormonally sensitive smooth muscles of the mesometrium 3 . Distinction between the two types is difficult as histopathology and immunohistochemical features are identical for all estrogen receptor‐positive leiomyoma of Mullerian derivation 5 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A review of the literature demonstrates 19 cases of degenerated fibroids that were misdiagnosed as an ovarian malignancy on imaging prior to surgery [6][7][8][9]. the left sidewall to the para-vesicle space.…”
Section: Introductionmentioning
confidence: 99%